The effect of complainant's perception ofjustice on their satisfaction and future behavior: An empirical study in North Cyprusfinancial service institutions - Ayrom, Shabnam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: The main purpose of this study is to examine customer complaint satisfaction and its effect on attitude and behavioural intensions of customers in banking sector of TRNC. The conceptual model was tested by using a questionnaire with 57 questions. While developing questionnaire in depth literature analyses were carried out. Model aims to measure how different organizational responses to complaints influence complainants‟ distributive, procedural, and interactional justice perceptions; the effects of complainants‟ perceptions of distributive, procedural, and interactional justice on their satisfaction; the effects of complaint satisfaction on trust and commitment; the effects of trust and commitment on word of mouth and rework intensions. Among collected questionnaires 250 questionnaires find usable. The finding of this study showed that there is no positive relationship between facilitation and procedural justice; apology and explanation with interactional justice; procedural justice with complaint satisfaction. The rest of the hypotheses were supported. The structural equation modelling analysis was carried out and findings are presented. Study also presented managerial implications and recommendations for bank managers to manage complain. Keywords: Justice theory, complaint satisfaction, banks, post purchase behaviour, TRNC. ………………………………………………………………………………………………………………………… ÖZ: Bu çalışmanın esas amacı TRNC‟de faaliyet gösteren banka müşterilerinin şikayetlerinin nasıl çözümlendiğini ve onların bankaya karşı tutum ve ileriye yönelik davranışlarını incelemektir. Bu amaçla oluşturulan kavramsal modeli test etmek amacı ile oluştutulan anket 57 yargı cümlesinden oluşmaktadır. Anketin oluştutulmasında detaylı literatür taraması yapılmıştır. Oluşturulan model ile kurumun şikayetlere karşı vermiş olduğu cevapların müşterilerin dağıtımsal, işlemsel ve etkileşimsel adalet algıları üzerindeki etkisi; bu algıların şikayetin giderilmesi ve memnuniyet oluşumu üzerindeki etkisi; oluşan memnuniyetin müşterilerin güven ve bağlılığı üzerindeki etkisi; oluşan güven ve bağlılığın müşterilerin tavsiye etme ve tekrar birlikte çalışma niyetleri üzerindeki etkileri araştırılmaktadır. Bu amaçla yürütülen anket çalışması sonucunda toplanan verilerden 250 adeti kullanabilir olarak kabul edilmiştir. Çalışmanın sonuçları doğrultusunda yardımcı olma değişkeni ile işlemsel adalet algısı, özür ve açıklama değişkenleri ile etkileşimsel adalet algısı ve işlemsel adalet ile şikayet tatmini arasında pozitif bir ilişkinin olmadığı, ancak diğer tüm hipotezlerin kabul edilidiği görülmektedir. Çalışmada yapısal eşitlik modellemesi analizi yapılmıştır. Çalışmada idari uygulamalar ve banka yöneticilerine yönelik tavsiyelerde yer almaktadır. Anahtar Kelimeler: Adalet teorisi, şikayet tatmini, bankalar, ileriye yönelik tutum, TRNC.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2013. Supervisor: Prof. Dr. Halil Nadiri.
Keywords: Business Administration; Banks and Banking - Customer relations - Cyprus, North; Bank Customers - Customer satisfaction - Cyprus, North; Justice Theory Complaint Satisfaction Banks Post Purchase Behaviour TRNC